2016
DOI: 10.1016/j.diii.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous thermal ablation of primary lung cancer

Abstract: Percutaneous ablation of small-size non-small-cell lung cancer (NSCLC) has demonstrated feasibility and safety in nonsurgical candidates. Radiofrequency ablation (RFA), the most commonly used technique, has an 80-90% reported rate of complete ablation, with the best results obtained in tumors less than 2-3cm in diameter. The highest one-, three-, and five-year overall survival rates reported in NSCLC following RFA are 97.7%, 72.9%, and 55.7% respectively. Tumor size, tumor stage, and underlying comorbidities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 48 publications
2
47
0
2
Order By: Relevance
“…In some medical institutions, the treatment is offered as an outpatient procedure. Patients with pretreatment pulmonary dysfunction may experience temporary exacerbation of respiratory symptoms after ablation and require oxygen therapy lasting one day to three weeks . It is difficult to clearly define the lowest threshold of pulmonary reserve that can tolerate percutaneous pulmonary thermal ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some medical institutions, the treatment is offered as an outpatient procedure. Patients with pretreatment pulmonary dysfunction may experience temporary exacerbation of respiratory symptoms after ablation and require oxygen therapy lasting one day to three weeks . It is difficult to clearly define the lowest threshold of pulmonary reserve that can tolerate percutaneous pulmonary thermal ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pretreatment pulmonary dysfunction may experience temporary exacerbation of respiratory symptoms after ablation and require oxygen therapy lasting one day to three weeks. 22 It is difficult to clearly define the lowest threshold of pulmonary reserve that can tolerate percutaneous pulmonary thermal ablation. de Baere et al reported that they successfully performed percutaneous lung RFA in a patient with a forced expiratory volume in one second (FEV1) of <0.8 L/s.…”
Section: Discussionmentioning
confidence: 99%
“…Current ablation modalities frequently used include MWA, cryoablation, and irreversible electroporation (IRE). 20 RFA and MWA both achieve controlled heating at the tip of the applicator, which leads to tissue coagulation necrosis and tissue death. RFA achieves this through a rapid alternating electric current that is transmitted through the RFA applicator into the lesion and back to the RFA generator through grounding pads or a grounding electrode.…”
Section: Lung Malignancymentioning
confidence: 99%
“…Recent studies have shown that following RFA, early‐stage NSCLC patients who cannot tolerate surgical resection (tumor diameter ≤ 3 cm) have one, three, and five‐year survival rates of 90%, 70%, and 50%, respectively, and a mortality rate of < 2% . This clinical evidence leads us to believe that RFA may become a new treatment modality following surgery, radiotherapy, and systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that following RFA, early-stage NSCLC patients who cannot tolerate surgical resection (tumor diameter ≤ 3 cm) have one, three, and fiveyear survival rates of 90%, 70%, and 50%, respectively, and a mortality rate of < 2%. 72 This clinical evidence leads us to believe that RFA may become a new treatment modality following surgery, radiotherapy, and systemic therapy. However, the efficacy of RFA still needs to be validated in prospective, randomized, multi-center clinical trials, 73 and comparison with other treatment, including surgery, [74][75][76][77] ablation 78 and SBRT [79][80][81][82] is necessary.…”
Section: Discussionmentioning
confidence: 99%